Pretransplant IgA-Anti-Beta 2 Glycoprotein I Antibodies As a Predictor of Early Graft Thrombosis after Renal Transplantation in the Clinical Practice: A Multicenter and Prospective Study - Morales, Jose M.; Serrano, Manuel; Martinez-Flores, Jose Angel; Gainza, Fracisco Javier; Marcen, Roberto; Arias, Manuel; Escuin, Fernando; Pérez, Dolores; Andres, Amado; Martínez, Miguel Angel; Maruri, Naroa; Alvarez, Eva; et al. (Frontiers in Immunology, 2018)
Background. Graft thrombosis is a devastating complication after renal transplantation. We recently described the association of anti-Beta-2-Glycoprotein-I (IgA-ab2GP1) antibodies with early graft loss mainly caused by thrombosis in a monocenter study. Methods. Multicenter prospective observational cohort study. Setting & Participants Seven hundred forty patients from five hospitals of the Spanish Forum Renal Group transplanted from 2000-2002 were prospectively followed-up for ten years. Outcomes Early graft loss and graft loss by thrombosis. Measurements The presence of IgA anti-B2GP1 antibodies in pretransplant serum was examined using the same methodology in all the patients. Results At transplantation, 288 patients were positive for IgA-B2GP1 (29%, Group-1 and the remaining were negative (Group-2). Graft loss at 6 months was higher in Group-1 (12.5% vs 4.2% p˂0.001), vessel thrombosis being the most frequent cause of early graft loss, especially in Group-1 (6.9% vs 0.4% p ˂0.001). IgA-aB2GP1 was the most important independent risk factor for graft thrombosis (HR: 13.83; 95% CI: 3.17 to 60.27, p ˂0.001). Furthermore, the, presence of IgA-aB2GP1 was associated with early graft loss and delayed graft function. At ten years, survival figures were also lower in Group-1: graft survival was lower compared with Group-2 (60.4% vs 76.8% p<0.001). Mortality was significantly higher in Group 1 (19.8 % vs 12.2%, p=0.005). Limitations Patients were obtained during a three year period (1 January 2000-31 December 2002) and kidneys were only transplanted from brain-dead donors. Nowadays, the patients are older and the percentage of sensitized and retransplants is high. Conclusions. In a prospective observational multicenter study, we were able to corroborate that pre-transplant presence of IgA-aB2GP1 was the main risk factor for graft thrombosis and early graft loss. Therefore, a prospective study is needed to evaluate the efficacy and safety of prophylactic anticoagulation to avoid this severe complication.